PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN PADA PERUSAHAAN AGRIKULTUR SUB SEKTOR PERKEBUNAN YANG TERDAFTAR DI BEI PERIODE TAHUN 2015-2019 - Iroh Rahmawati; Putri Kitrianti (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2021)
This study aims to determine the effect of Good Corporate Governance which consists of the Audit Committee Size as Variable on the Company's Financial Performance which is calculated using Return On Assets. This study was conducted on Agricultural Sub Sektor companies listed on the Indonesia Stock Exchange in 2015-2019. Samples were taken using purposive sampling technique. The number of samples is 9 companies with 5 years of financial reports. The method of analysis used in this study is a simple linear regression method. The results of this study indicate that Good Corporate Governance (Audit Committee Size) has a significant effect on Company Financial Performance (ROA) with value of tcount is 2.194 and ttable is 2.016, for sig. 0.034. And the value of R Square Good Corporate Governance on the Company's Financial Performance is 10.1% while 89.9% is influenced by other variables which are not discussed in this study.